JANDA DESA OAN MANE (STUDI FENOMENOLOGI DI KECAMATAN MALAKA BARAT KABUPATEN MALAKA) - Bere, Merlince; Klau, Erni Raster; Sogen, Yosephina K (Universitas Nusa Cendana, 2024)
Abstract This study aims to determine widows in Oan Village in maintaining daily family economic survival through ikat weaving in the Taru Manu Oan Weaving Group, focusing this research on the concept of widowhood as a result of divorce and death how the ability of widows in Oan Mane Village to carry out economic life in Oan Mane Village, West Malacca District, Malacca Regency. which is carried out to reveal the nature of individual experience through phenomenological approaches, observation, interviews and documentation studies. The subjects were selected as many as 8 (eight) people because the research focused on widows in Oan Mane Village in improving family economic needs through the ikat weaving program in the Taru Manu Oan weaving group. The results of this study show that the main business carried out is a program of ikat weaving empowerment in the Taru Manu Oan weaving group and this weaving group is only given to widows in Oan Mane Village to meet the daily economic needs of the family and the cost of children's school needs. The income obtained is also normal because the price is seen from the fabric woven if it is patterned and marobo and ordinary the price varies, but they are satisfied with the producers obtained from this woven cloth sold. For this reason, they are very grateful to the Malacca Regency Government for presenting a weaving program which has helped in increasing the daily economic needs of families.